INTEGRATION OF GUIDANCE AND CONTROL SYSTEMS USING PATH FOLLOWING METHOD IN HYBRID UNDERWATER GLIDER - Fadhil Djauhari, Ibrahim
Hybrid Underwater Glider (HUG) is a type of Autonomous Underwater Vehicle (AUV) that can perform gliding and propulsion movements. One of the main missions of the HUG is bathymetry or underwater mapping. However, HUG faces a high risk of damage while operating under water caused by collision with static underwater obstacles. Therefore, a system in the HUG is needed to make a path between the waypoints and move the HUG to follow said path. The system will implement the Path Following guidance goal by integrating the guidance and control system in HUG. The guidance system functions to create a path between each waypoint and direct the HUG to follow the path, while the control system funcions to move the actuators within the HUG to follow said path. The systems implemented in software form using ROS and in hardware form in ITB-HUG. The results with HILS show that ITB-HUG can perform a 1000 m long and 100 m deep gliding movement as well as a 50x50 m2 lawnmower pattern with a maximum crosstrack error of 6.269 m in the XY plane and 0.072 m in the XZ plane.